Uji Sensitivitas Kunyit Kuning dan Kunyit Putih Terhadap Bakteri Pencemar Susu - Rezica Kanza Nobiola; Tusy Triwahyuni; Nia Triswanti; Efrida Warganegara (Puslitbang Sinergis Asa Professional, 2020)
Yellow turmeric (Curcuma longa) and white turmeric (Kaempferia rotunda) are one of the medicine plants and seasons that are used by most of the people. Turmeric belongs to the zingiberaceae family as a medicinal plant that is known to contain antibacterial substances. Antibacterial ingredients in turmeric, namely are curcuminoids and essential oils which are believed to be able to kill and inhibit bacteria. The purpose of this study is to know the sensitivity of yellow turmeric and white turmeric to milk contaminating disease using the Kirby Bauer method with a diffusion disk technique. The study design using experimental technique. Yellow turmeric rhizome extract and white turmeric were tested to the milk contaminating disease using diffusion disk technique with 12,5%, 25%, 50%, and 100% concentration. Yellow turmeric rhizome extract with 12,5%, 25%, 50%, and 100% concentration showed results inhibition diameter zone: 0 mm, 11,3 mm, 15,3 mm, and 17 mm. On the other hand, white turmeric gets no result in the inhibition diameter zone for all concentration. This study showed there is a sensitivity of yellow turmeric to bacteria of milk-contamination that causes foodborne disease using the Kirby Bauer method with white turmeric disk diffusion technique. There is no sensitivity to bacteria of milk-contamination that causes foodborne disease using the Kirby Bauer method with disk diffusion technique